2016
DOI: 10.1007/s00247-016-3721-9
|View full text |Cite
|
Sign up to set email alerts
|

Conversion and reliability of two urological grading systems in infants: the Society for Fetal Urology and the urinary tract dilatation classifications system

Abstract: Correspondence between the systems was poor using a recommended re-categorization (SFU-A). An alternative re-categorization (SFU-B) was found to be more appropriate for establishing correspondence between the systems. Both systems were reliable, with good intra- and inter-observer agreement for the assessment of infant kidneys, but the UTD system had better inter-observer agreement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Han et al . evaluated the reliability of the UTD and SFU grading system for postpartum urinary dilatation in infants [ 19 ]. As a result, they said that the UTD system had a better agreement between the observers.…”
Section: Discussionmentioning
confidence: 99%
“…Han et al . evaluated the reliability of the UTD and SFU grading system for postpartum urinary dilatation in infants [ 19 ]. As a result, they said that the UTD system had a better agreement between the observers.…”
Section: Discussionmentioning
confidence: 99%
“…The SFU grading system is similar to other scoring systems for hydronephrosis, such as the urinary tract dilation classification system. 24 A multidisciplinary panel of 9 members was convened to reach consensus on the lowest threshold of abnormalities that should be deemed important to identify at the time of first febrile UTI. The investigative team anchored each threshold to a clinical meaning to assist the panel.…”
Section: Discussionmentioning
confidence: 99%
“…Renal pelvis AP diameter is the only quantitative criteria in UTD classification. However, other studies have shown that AP diameter does not make any significant predictive impact in terms of prognosis compared to other parameters (40,41). A comparison of UTD and SFU grading system for their ability to predict time to hydronephrosis resolution showed that cumulative resolution rate at 3 years was higher in SFU grades (43).…”
Section: Parameters Determining Poor Prognosis In Prenatal Upjhnmentioning
confidence: 90%
“…Both is proposed to be used regardless of etiology of hydronephrosis. Several studies have shown that inter-observer reliability of UTD classification is superior to SFU classification ( 41 , 42 ). The use of other urinary system ultrasound parameters (kidney echogenicity, ureter dilation, ureterocele, oligohydramnios) in UTD classification increases its reliability.…”
Section: Parameters Determining Poor Prognosis In Prenatal Upjhnmentioning
confidence: 99%